Feasibility of a pioneer social service treatment for gambling disorder-The first 6-month follow-up data - C. Grudet; G. Åkesson; K. Wennerstrand; A. Håkansson (Elsevier, 2024)
Gambling disorder can be treated with cognitive behavioral therapy (CBT), but treatment is under-dimensioned in many settings. For example, in Sweden, a setting with mixed responsibility for addiction treatment between health care and social services, treatment for gambling disorder has only recently been introduced in the responsibilities of public institutions. After the introduction of gambling in treatment legislation in 2018, few studies have assessed the real-world feasibility of such treatment. In addition, treatment in social services specifically has not been documented or evaluated, and therefore, in a pioneer gambling treatment facility in such a setting, this study aimed to investigate treatment outcome in patients with gambling disorder six months after completed CBT treatment within a social service setting. Twenty patients receiving CBT treatment during 2018-2020 were followed with respect to gambling habits at end of treatment and at follow-up six months after treatment. The National Opinion Research Center DSM Screen for Gambling Problems (NODS) was used as screening tool. Rates of gambling abstinence, as well as subjective experience of the treatment, are reported. Ninety percent of the patients were abstinent from gambling at six-month follow-up, and 95 percent of the patients no longer fulfilled criteria of a gambling disorder. In conclusion, these pilot results suggest that CBT treatment is a feasible method for treatment of gambling disorder also in a social service setting. However, due to the limited sample size of this pilot study, and the limited background information of clients who could not be reached, future studies with larger sample sizes are needed.